Islamic Education Policy in Improving Access to Education for Marginalized Communities in Indonesia: Kebijakan Pendidikan Islam dalam Meningkatkan Akses Pendidikan bagi Masyarakat Marjinal di Indonesia - Khairanis, Retisfa (Yapilin Press, 2025)
Access to education for marginalized communities in Indonesia still faces various geographical, economic, and social barriers. This research aims to analyze how Islamic education policy plays a role in improving access to education for marginalized groups, especially through Islamic education institutions such as madrasah and Islamic boarding schools. This research uses a qualitative approach with a literature review method that examines various secondary sources from journals, policy reports, and relevant official data. The results show that Islamic education policy has made a real contribution in expanding the reach of education in the 3T areas (underdeveloped, frontier, and outermost). Madrasahs and pesantren have become an alternative education that is easily accessible to marginalized communities, especially because they are located in remote areas. In addition, government programs such as the School Operational Assistance (BOS) and the Smart Indonesia Program (PIP) also support the continuation of education for children from underprivileged families. However, there are still inequalities in the quality of education and facilities available in Islamic education institutions in remote areas. Therefore, in addition to expanding access, future policies need to focus on improving the quality of education equally.